A critical review of natural products driven correction of bile acid dysregulation: a therapeutic strategy for nonalcoholic fatty liver disease - Peng, Qing; Hao, Liyuan; Li, Shenghao; Yu, Fei; Li, Na; Hu, Xiaoyu (Frontiers in Pharmacology, 2025)
Nonalcoholic fatty liver disease (NAFLD) represents a significant global health challenge. While two drugs (semaglutide, resmetirom) have recently been approved for nonalcoholic steatohepatitis (NASH), their clinical utility is constrained by gastrointestinal side effects, insufficient efficacy against fibrosis, and dose-related adverse events. Similarly, obeticholic acid (OCA), a farnesoid X receptor (FXR) agonist with antifibrotic potential, is associated with significant side effects, including severe pruritus. Dysregulation of bile acid (BA) metabolism is a central driver of NAFLD progression, characterized by imbalances in synthesis, impaired enterohepatic circulation, and aberrant nuclear receptor signaling. Certain hydrophobic BAs contribute to hepatocyte apoptosis, oxidative stress, and inflammation, thereby exacerbating liver injury. Targeting BA homeostasis is thus a promising therapeutic strategy, with natural products emerging as attractive candidates due to their multi-target actions and favorable safety profiles. This review summarizes 10 major classes of natural products, including traditional Chinese medicine (TCM) formulas, flavonoids, saccharides, saponins, alkaloids, curcuminoids, lignans, iridoid glycosides, sterols/terpenoids, and phenolic acids/other phenolics, that alleviate NAFLD by regulating BA metabolism. These agents modulate BA-sensing receptors, reshape the gut microbiota to optimize BA conversion, and regulate key BA transporters and enzymes. Compared with synthetic drugs, natural products offer broader efficacy, lower toxicity, and greater adaptability to the heterogeneity of NAFLD. However, significant limitations persist. Preclinical studies rely heavily on single-sex rodent models, while clinical evidence remains inconsistent. Crucially, mechanistic causality, such as the interplay between the gut microbiota and BAs, lacks rigorous validation through methods like fecal microbiota transplantation (FMT) or gene knockout studies. Furthermore, challenges in metabolite standardization and dose rationality hinder clinical translation. Future research must prioritize human-relevant models, large-scale randomized controlled trials (RCTs) with histological endpoints, and robust causal validation. By addressing these gaps, natural products targeting BA metabolism hold great promise to complement or replace existing therapies, offering safer and more effective personalized treatments for NAFLD.